Covid-19 and household financial : a study among UKM undergraduate - Ahmad Nurnaqib Nasharuddin,; Wong, Wai-Yan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The pandemic of a life-threatening disease better known as COVID-19 has spread rapidly since December 2019. The COVID-19 outbreak in Malaysia started as a small wave of 22 cases in January 2020 through imported cases. It was followed by larger waves mainly from local transmissions resulting in 651 cases. This caused the government to start acting by implementing the Movement Control Order (MCO) to reduce the spread of the epidemic. The implementation of MCO has disrupted many businesses, causing the economy to be affected. While most studies concentrate on the economic impact of COVID-19 on the country or industry, one group seems to be left out – the undergraduates. This preliminary study was conducted for the purpose of examining the impact of the COVID-19 pandemic on the household financial position of undergraduates in Malaysia. In addition, this study also aims to look at the level of financial management of undergraduates during the COVID-19 pandemic. This survey study uses a questionnaire instrument to obtain information. The respondents of the study consist of 107 undergraduates. Our findings showed that, on average, UKM undergraduates were not too badly affected during this outbreak. The findings also indicate the importance of financial knowledge in helping to strengthen the household financial position. Therefore, undergraduates are advised to strengthen their financial knowledge and management to enable them to manage their personal finances better to buffer the effect of financial disasters.